PERAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL PEMODERASI PADA PENGARUH KONFLIK PEKERJAAN KELUARGA TERHADAP KESEJAHTERAAN - Rikha Muftia Khoirunnisa; Desta Rizky Kusuma; Mustika Rahmi (Universitas Ahmad Dahlan, 2023)
Work and family life are two domains of human activity where people spend two-thirds of their lives in these two domains. Each individual has a role in each of these domains and strive to be able to fulfill its role. However, when one role demands more attention it will interfere with the fulfillment of the other role. This study aims to determine the effect of work-family conflict on welfare. Then this study will examine the role of moderating emotional intelligence on these influences. The sample in this study were all Ahmad Dahlan University Hospital employees, amounting to 104 people. The sampling technique used in this study is saturated sampling. The research data was obtained through a questionnaire filled out by Ahmad Dahlan University Hospital employees. Hypothesis testing uses multiple regression and multilevel regression (hierarchy). The results showed that work-family conflict and emotional intelligence affect welfare. However, the effect of moderating emotional intelligence on the effect of work-family conflict on well-being is not proven.